A novel efficient multiple encryption algorithm for real time images - Shima Ramesh Maniyath; Thanikaiselvan V. (Institute of Advanced Engineering and Science, 2020)
In this study, we propose an innovative image encryption Techniques based on four different image encryption Algorithm. Our methodology integrates scrambling followed by Symmetric and Asymmetric Encryption Techniques, to make the image meaningless or disordered to enhance the ability to confront attack and in turn improve the security. This paper mainly focused on the multiple encryption Techniques with multiple keys on a single image by dividing it into four blocks. So instead of using one Encryption method a combination of four different Encryption Algorithm can make our image more secure. The Encryption is done first by using DNA as secret key, second by using RSA, third by DES and fourth by Chebyshev. The pros and cons for all the Encryption methods are discussed here. Proposed methodology can strongly encrypt the images for the purpose of storing images and transmitting them over the Internet. There are two major benefits related with this system. The first benefit is the use of Different Algorithm with different keys. The second benefit is that even though we are using four different Algorithm for a single image, the time taken for encryption and decryption is few seconds only. Our method is methodically checked, and it shows an exceptionally high level of security with very good image quality.